RISING STAR INDONESIA DI RCTI: Mediatisasi Vote dalam Menentukan Nasib Kontestan - Fauzi, Abas (Seni Media Rekam ISI Surakarta, 2016)
Nowadays,the influences of televise program to audience is stronger.Therefore,media owners have to make some strategies to captivate the forum. Programs areincluding entertainment, news information, and education. Compared with the past,entertainment program is bigger than education program. Moreover, there are SingerGot Tallent programs broadcasted on televise stations, for example RCTI with RisingStar Indonesia program.This program was adapted by Rising Star from United State.Thisprogram uses telephone and vote to get the applicants or new singers. Vote as ameditation from audience to determine the applicants in the next step.Keywords: Rising Star Indonesia, RCTI, vote meditation, and new singer.